2017
DOI: 10.1007/s11414-017-9583-6
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Peer Support: Results of a Qualitative Study

Abstract: Peer-delivered services for individuals with psychiatric conditions are becoming an established part of the mental health workforce. Given the growing focus on evidence-based supported employment, peer specialists are often assisting individuals who are choosing, getting, or keeping employment. As part of a larger randomized clinical trial examining the effectiveness of an innovative intervention called vocational peer support, 13 semi-structured qualitative interviews were conducted to examine how recipients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Give the proven effectiveness of supported employment [12,13], peer support services have also been integrated into vocational rehabilitation systems for persons who experience severe mental illness [14,15]. During job matching, peer support services delivered as part of supported employment offer individualized assistance, and the preferences of persons with disabilities are always respected [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Give the proven effectiveness of supported employment [12,13], peer support services have also been integrated into vocational rehabilitation systems for persons who experience severe mental illness [14,15]. During job matching, peer support services delivered as part of supported employment offer individualized assistance, and the preferences of persons with disabilities are always respected [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Peer mentoring can also facilitate social connection that may be essential for the health, quality of life and participation of otherwise socially isolated young adults with IDD‐MH (Gidugu et al, 2015; Stalker et al, 2011). Evidence suggests peer supports uniquely foster social networks, normalize one's experiences and share strategies that promoted their own recovery—all of which can promote mental health, quality of life and participation (Balogun‐Mwangi, Rogers, Maru, & Magee, 2019; Foley et al, 2012; Gidugu et al, 2015; Kramer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Give the proven effectiveness of supported employment [12,13], peer support services have also been integrated into vocational rehabilitation systems for persons with psychiatric disabilities [14,15]. During the job match, peer support services delivered as part of supported employment offer individualized assistance, and the preferences of persons with disabilities are always respected [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Peer support workers draw from their own lived experiences to help persons with psychiatric disabilities overcome internalized stigma, lower self-esteem and/or self-e cacy at work [4,13]. Peer support workers also serve as role models for persons with disabilities, by exemplifying the positive outcome that is achievable if persons with disabilities tap into their own predilections, potential, and advantages for employment through self-determination [14,16]. An earlier study found that peer support worker's "lived experience" motivated persons with disabilities to engage in relationship-building and instilled in them a sense of normalcy, both of which facilitated the forming of mutual support and the pursuit of vocational goals by persons with psychiatric disabilities [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation